2021
DOI: 10.1021/acs.jpclett.0c03519
|View full text |Cite
|
Sign up to set email alerts
|

Near-Unity Photoluminescence Quantum Yield and Highly Suppressed Blinking in a Toxic-Metal-Free Quantum Dot

Abstract: There is no literature report of simultaneously achieving near-unity PLQY (ensemble level) and highly suppressed blinking (ultrasensitive single-particle spectroscopy (SPS) level) in a toxic-metal-free QD. In this Letter we report accomplishing near-unity PLQY (96%) and highly suppressed blinking (>80% ON fraction) in a toxic-metal-free CuInS 2 / ZnSeS Core/Alloy-Shell (CAS) QD. In addition, (i) gigantic enhancement of PLQY (from 15% (Core) to 96% (CAS QD)), (ii) ultrahigh stability over 1 year without signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 42 publications
0
68
0
Order By: Relevance
“…Thus far, there are many reports on suppressed PL blinking behavior of alloyed QDs. [26,[139][140][141] In 2009, Wang et al [26] studied the single QD PL intensity time traces of CdZnSe/ZnSe alloyed core/shell QDs and CdSe/ZnSe core/shell QDs. It has been found that CdZnSe/ZnSe alloyed core/shell QDs exhibit complete suppression of PL blinking, whereas CdSe/ZnSe core/ shell QDs show PL blinking.…”
Section: Suppressed Pl Blinkingmentioning
confidence: 99%
“…Thus far, there are many reports on suppressed PL blinking behavior of alloyed QDs. [26,[139][140][141] In 2009, Wang et al [26] studied the single QD PL intensity time traces of CdZnSe/ZnSe alloyed core/shell QDs and CdSe/ZnSe core/shell QDs. It has been found that CdZnSe/ZnSe alloyed core/shell QDs exhibit complete suppression of PL blinking, whereas CdSe/ZnSe core/ shell QDs show PL blinking.…”
Section: Suppressed Pl Blinkingmentioning
confidence: 99%
“…Larger k d values compared to k t have been reported earlier in several semiconductor QD systems indicating that the trapped electron stays only for a shorter duration in the trap-states. 43,45 Semiconductor QDs such as CdSe and PbS possess shallow trap-states, and the depth of the trap-state increases as the core size decreases. 10,25 In other words, the energy gap between the trap-state and the conduction band edge in CdSe QDs having a smaller core size is wider compared to QDs having a large size.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Semiconductor QDs exhibit mysterious episodes of emission intermittency often called blinking when explored using single-particle PL spectroscopy. Indeed, blinking is a universal feature of all single emitters. This is manifested as a finite occurrence of emission, followed abruptly by periods wherein no light is emitted. These extreme states are narrated as ON-states (bright) and OFF-states (dark). In the OFF-state, QDs lose the absorbed energy through nonradiative pathways instead of emitting photons and are hence considered as a disadvantage for various applications. , Apart from the completely dark state, a low-intensity gray state is also observed during the blinking process .…”
Section: Introductionmentioning
confidence: 99%
“…Because of their great potential in diverse applications like in photovoltaics, LEDs, display technologies, lasing, and so on, the cesium lead halide (CsPbX 3 , X = Cl, Br, I) perovskite NCs continue to receive great attention of the researchers. High PLQY and ease of tunability of the PL band position across the entire visible region make these substances quite attractive for optoelectronic applications. ,, In this family of perovskites, CsPbCl 3 and CsPb­(Cl/Br) 3 NCs are considered indispensable due to their violet and blue emission, which are essential color components for fabrication of white LEDs. Unlike the conventional metal chalcogenide semiconductor NCs, the halide perovskites generally exhibit high PLQY due to their defect-tolerant nature. , However, compared to their green- and red-emitting counterparts, CsPbBr 3 and CsPbI 3 , the large-bandgap perovskites such as violet- and blue-emitting CsPbCl 3 and CsPb­(Cl/Br) 3 NCs most often exhibit much lower PLQY due to competing nonradiative recombination of the photogenerated charge carriers through the deep trap states generated by halide vacancies and distorted [PbX 6 ] 4– octahedral units. ,, Since the first synthesis of these NCs by the hot-injection (HI) method, several methodologies have been developed for the preparation of violet- and blue-emitting CsPCl 3 and CsPb­(Cl/Br) 3 NCs with higher PLQY. ,, Doping with different bivalent metal ions ,,,,,,,, and a variety of postsynthetic treatments of the as-synthesized NCs ,,,,,, are the most common practices for improving the PLQY of these NCs. Considering that, in the first synthesis of the CsPbX 3 NCs PbX 2 was used as pr...…”
Section: Introductionmentioning
confidence: 99%